2022
DOI: 10.3390/healthcare10101933
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mobile Health (m-Health) Education Based on WANTER Application on Knowledge, Attitude, and Practice (KAP) Regarding Anemia among Female Students in a Rural Area of Indonesia

Abstract: Female students, as adolescent girls, are more at risk of anemia because of high nutritional requirements. Health education through mobile applications influences the knowledge, attitude, and practice (KAP) of anemia in adolescent girls. Based on our previous study, several adolescents experienced anemia. This study aims to analyze the effect of health education through mobile applications, namely the WANTER application, on increasing KAP. This study was quasi-experimental with a pretest–posttest design; the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
(29 reference statements)
1
0
0
Order By: Relevance
“…In concordance with the results of this study, a recent trial in Indonesia showed that nutrition education affected improving knowledge about exclusive breastfeeding (Setyowati, Rohaya and Rahmawati, 2023). Another study about the effect of mobile health education regarding anemia among female students implies that adolescents' knowledge increased significantly in three months after the intervention (Sari, Herawati, Dhamayanti, Ma'ruf, et al, 2022). Study about health education for obesity risk reduction among junior high school student state that participants in the intervention group had better knowledge regarding physical activity and diet (Rizvi, Kumar, Kulkarni, & Kamath, 2022).…”
Section: Resultssupporting
confidence: 89%
“…In concordance with the results of this study, a recent trial in Indonesia showed that nutrition education affected improving knowledge about exclusive breastfeeding (Setyowati, Rohaya and Rahmawati, 2023). Another study about the effect of mobile health education regarding anemia among female students implies that adolescents' knowledge increased significantly in three months after the intervention (Sari, Herawati, Dhamayanti, Ma'ruf, et al, 2022). Study about health education for obesity risk reduction among junior high school student state that participants in the intervention group had better knowledge regarding physical activity and diet (Rizvi, Kumar, Kulkarni, & Kamath, 2022).…”
Section: Resultssupporting
confidence: 89%
“…Berdasarkan penelitian AC Nielsen, Indonesia menduduki peringkat kedua sebagai negara terkonsumtif di dunia (Khosravani et al, 2017). Perkembangan modernisasi dan teknologi juga memberikan dampak signifikan terhadap perilaku konsumtif, di mana perilaku tersebut telah menjadi sesuatu yang dianggap wajar di tengah masyarakat (Sari et al, 2022).…”
Section: Pendahuluanunclassified
“…Perbedaan gaya hidup antara mahasiswa rural dan urban juga dapat tercermin dalam pola konsumsi mereka (Sari et al, 2022). Mahasiswa rural cenderung lebih mengandalkan produk dan makanan lokal yang tersedia di daerah mereka.…”
Section: Analisis Perbedaan Gaya Hidup Mahasiswa Urban Dan Ruralunclassified
“…Organisasi Kesehatan Dunia atau World Health Organization (WHO) mendefinisikan remaja sebagai periode dari usia 10 hingga 19 tahun. Masa remaja adalah masa di mana perubahan fisik, psikologis dan kognitif bertumbuh dan berkembang dengan sangat cepat (Sari et al, 2022). Pada masa tersebut, masalah gizi yang umum terjadi di antaranya obesitas, kekurangan energi kronis (KEK), dan anemia.…”
Section: Pendahuluanunclassified